Peran Badan Penyelesaian Sengketa Konsumen (BPSK) dalam Menyelesaikan Sengketa Finance di Kota Gorontalo - Moh. Alfajar Mursidah; Nirwan Junus; Sri Nanang M. Kamba (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
A situation that is very unbalanced between consumers and business actors is a big potential that can lead to disputes between consumers and business actors. The government has issued laws that regulate consumer protection, in particular Law Number 8 of 1999 concerning Consumer Protection. The goal is to provide protection to consumers. This research is intended to: (1) to find out the role of the Consumer Dispute Settlement Agency (BPSK) in resolving Finance disputes (2) to find out what are the obstacles faced by the Consumer Dispute Settlement Agency (BPSK) in resolving Finance disputes. This research uses the type of empirical legal research, using a literature approach and research in the field. The sources of legal materials used are primary legal materials and secondary legal materials.The results of the study show that first, the Gorontalo City Consumer Dispute Settlement Agency (BPSK) has carried out its role, totaling 11 (eleven) of which is resolving consumer disputes in 3 (three) ways, namely mediation, conciliation and arbitration, opening consultations on consumer protection, if there is a violation the Consumer Protection Act (UUPK) the Consumer Dispute Settlement Agency (BPSK) is required to report to investigators, the Consumer Dispute Settlement Agency (BPSK) is required to receive complaints in writing or in writing, the Consumer Dispute Settlement Agency (BPSK) is tasked with conducting inspections and research related to consumer disputes, BPSK summons business actors suspected of violating the Consumer Protection Act (UUPK), the Consumer Dispute Settlement Agency (BPSK) has the right to present expert witnesses, witnesses or someone who is deemed to know of violations of the Consumer Protection Act (UUPK), examine the truth evidence, ascertaining whether or not there is a loss on the part of the consumer. The second research result is, What obstacles are faced by BPSK Gorontalo City in resolving Finance disputes in Gorotanlo City, these obstacles are divided into two parts, namely Internal and External. For internal ones, there is an inclusion of a standard clause, asking for help from investigators to summon business actors who do not want to attend invitations from the Gorontalo City Consumer Dispute Settlement Agency (BPSK), finally, financial constraints, namely the Gorontalo City Consumer Dispute Settlement Agency (BPSK) still cannot manage their funds in grants (self-managed).